Young adult fisherfolks lifestyle, views toward the sea and other fishing related activites and life aspirations. - Laurente, Juhn Bob T.
The study sought to describe the lifestyle, views toward the sea and other fishing related activities and life aspirations of young adult fisherfolks. Seventy eight (78) respondents from 18 -30 years old were conveniently sampled from Brgy. Dumulog and Brgy. Culasi of Roxas City, Capiz., An interview schedule was administered to study the variables under investigation. Rresults revealed that young adult fisherfolks as early as five years old are active in fishing catching, processing and marketing. In terms of their leisure activities, ball games and social gatherings are preferred. They perceived the sea as bountiful and important in providing food and work for their family and community. Health, relationships and community ranked as the top most important, likely attained and moderately achieved life aspirations.